IMPROVING ACTIVE LEARNING THROUGH STUDENTS’ POWERPOINT PRESENTATIONS ON REPORT TEXT SPEAKING SKILL - Ahmila Novita (Universitas Islam Negeri Walisongo Semarang, 2016)
This study was carried out to improve active learning through students’ PowerPoint presentations on report text speaking skill in the third grade students of class 9A of SMP N 1 Bandungan2014/2015 academic year. The method used in this study was Classroom Action Research (CAR) which consists of planning, acting, observing, and reflecting. The study was carried out in two cycles. Each cycle consisted of one meeting 200 minutes (block schedule). The data of this study was gathered through: (1) Student’ presentations, (2) observations, and (3) students consultation. The result of the study showed that there was improvement of active learning in the teaching and learning process of class 9A; 100% was active in group work, 100% was active in consulting their difficulties with the teacher, 79.2% was active in finding resources of report text material, 87.5% was active in asking questions and 90% was active in answering questions. From the last two indicators can be seen that there is improvement of the active learning of students’speaking skill in asking and answering questions. In conclusion active learning through students’ PowerPoint presentations could increase the active teaching and learning process of class 9A, especially on their report text speaking skill.